A neologia semântica como processo de formação de palavras: implicações no ensino de língua portuguesa - Tainá Marcelle Silva Moreira (2020)
The objectives of this work are twofold, it seeks to recognize and to reaffirm semantic neologisms as a process of word formation in Brazilian Portuguese, as well as to discuss the contributions of studying the matter at hand for developing the lexical competence of high school students, which is the competence involved on the recognition, interpretation and ability to create new words and establish connections between words and word formation processes. Semantic neologisms are the results of the process of creating new words using morphological and phonological structures already found in the language changing their meaning and only their meaning. The new found meaning of the words resultant of this process may or may not be related to the meanings previously attached to the lexical items now transformed. Being that the case, the words will have a polysemic relation, otherwise the words are considered homonyms. The semantic neologisms found in this work were collected from advertisements printed on the news magazine Veja from 2015 to 2017. Advertisements are a great source of neologisms given that they tend to be expressive on their ways of communicating to and persuading their target audiences, and therefore are a good fit for the purposes of this research as well as for use in the classroom, since advertisements are ever so present on the lives of the students in a multiplicity of ways, providing relevant material for the development of critical reading in the classroom. As far as bringing the discussion about the relevance of studying the lexicon in the classroom, this work shows the marginal approach curently given to the matter despite its presence on the BNCC, which is the main document that dictates the curriculum of Brazilian schools. Finally, this work proposes some classroom activities that use semantic neologisms as tool for the development of the lexical competence of students.